An exploration of disaster risk to cultural heritage assets: towards effective conservation - Mansir, Dodo; Kasim, Narimah; Mat Radzuan, Indera Syahrul (International Journal of Conservation Science, 2018)
Owning to the losses incurred from the occurrence of certain events at Cultural Heritage Sites (CHS’s), conservation of its Cultural Heritage (CH) assets is reported to be threatened. The losses while qualifying for disasters to an affected CHS have necessitated proactive measures in the conservation of CH assets (individual and collective) aimed at reducing the risks of their exposure to eventual disasters. Foremost in such measures is the assessment of Disaster Risks (DR) whereby good practice (assessment of DR) conceptualises it (DR) to being a collective interplay of four variables namely: hazards, vulnerability; capacity and exposure. While deeper insights to the manifestation of each variable is deemed to be gained through a technique that investigates each variable in a multi-level approach, researches in the CH domain are yet to fully apply such approach (particularly to all the variables). Therefore, this research examined the four DR variables with a view to explore their multi-level manifestations in the domain of CH conservation. With the aid of a structured questionnaire and by means of conducting a survey, data was collected from 204 respondents at The Historic Commercial and Residential Zone (Old Quarter) of the Core Zone of Malacca CHS in Malaysia. Using IBM SPSS Statistics 23.0, a 5-Step Exploratory Factor Analysis (EFA) was carried out to analyse the inputted data. The achievement of certain threshold requirements by the results of this research indicates the fulfilment of some objectives of EFA. For instance, the reduction of manifest items is evident from the 47 manifest items having factor loadings ≥ 0.6 as against the total of 58 manifest items initially used in the study. Additionally, while the 47 manifest items for all 10 factors retained fulfilled convergent validity (loadings of manifest items ≥ 0.6), the loadings for the rotation of all 10 factors fulfilled discriminant validity (loading ≤ 0.3). These 10 factors retained spread across the four DR variables as follows: hazards (natural and human induced); vulnerability (human, material and managementbased); capacity (human, material and management-based); and exposure (heritage values and community assets). The EFA technique used in this research has enabled the multilevelling of each variable within the sphere of variable-to-factor and then factor-to-manifest item. The implication of the approach to multi-levelling of variables is for gaining deeper insights of DR to CHS conservation. However, it is worthy stating that the manifest items used in this study are bound to vary both within and across CHS’s, thus, further studies could embark on a conceptual framework for the assessment of DR that could apply to specific contexts of DR towards the effective conservation of CHS’s and its CH assets therein.